2006
DOI: 10.1002/macp.200600085
|View full text |Cite
|
Sign up to set email alerts
|

Melt Structure and its Transformation by Sequential Crystallization of the Two Blocks within Poly(L‐lactide)‐block‐Poly(ε‐caprolactone) Double Crystalline Diblock Copolymers

Abstract: Sequential crystallization of poly(L-lactide) (PLLA) followed by poly(e-caprolactone) (PCL) in double crystalline PLLA-b-PCL diblock copolymers is studied by differential scanning calorimetry (DSC), polarized optical microscopy (POM), wide-angle X-ray scattering (WAXS) and small-angle X-ray scattering (SAXS). Three samples with different compositions are studied. The sample with the shortest PLLA block (32 wt.-% PLLA) crystallizes from a homogeneous melt, the other two (with 44 and 60% PLLA) from microphase se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
122
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(140 citation statements)
references
References 28 publications
17
122
0
Order By: Relevance
“…This makes the crystallizable block copolymers representative systems having confined crystallization behavior, especially in the strong segregation regime [52]. Confined crystallization has been widely observed in the diblock copolymers having double crystalline blocks, such as PEO-b-PCL [112][113][114][115][116], PLLA-b-PEO [117][118][119][120][121][122], PLLA-b-PCL [123][124][125], poly(p-dioxanone) (PPDX)-b-PCL [126][127][128], polyolefin-based block copolymers [129][130][131][132][133][134][135], and so on. The confined crystallization kinetics and crystalline morphology of such block copolymers have been extensively studied.…”
Section: Crystalline Morphology Of Polymer Segments Confined In Blockmentioning
confidence: 99%
“…This makes the crystallizable block copolymers representative systems having confined crystallization behavior, especially in the strong segregation regime [52]. Confined crystallization has been widely observed in the diblock copolymers having double crystalline blocks, such as PEO-b-PCL [112][113][114][115][116], PLLA-b-PEO [117][118][119][120][121][122], PLLA-b-PCL [123][124][125], poly(p-dioxanone) (PPDX)-b-PCL [126][127][128], polyolefin-based block copolymers [129][130][131][132][133][134][135], and so on. The confined crystallization kinetics and crystalline morphology of such block copolymers have been extensively studied.…”
Section: Crystalline Morphology Of Polymer Segments Confined In Blockmentioning
confidence: 99%
“…Therefore the crystallized morphology formed by high-T m blocks is a kind of spatial confinement for the subsequent crystallization of low-T m blocks, which will be qualitatively different from the confinement imposed by amorphous or glassy microdomains observed in crystallineamorphous diblock copolymers. [9][10][11] There are some studies so far on the morphology formation of double crystalline block copolymers with different T m values, [12][13][14][15][16][17][18][19][20][21][22][23][24] where they are mainly focused on the characteristic morphology finally formed in the system.…”
mentioning
confidence: 99%
“…This crystallization-induced melting was first reported by Hamley et al 22 using a time-resolved WAXD method in a crystalline-crystalline diblock copolymer, poly(L-lactide)-block-poly("-caprolactone) (PLLA-b-PCL), where the primary crystallization of amorphous PCL blocks (lower-T m blocks) yielded the partial melting of pre-existing PLLA crystals (higher-T m blocks) just after quenching PLLA-b-PCL into low temperatures. They concluded that the melting of PLLA crystals occurred partially in order to compensate the space previously occupied by amorphous PCL blocks.…”
Section: Crystallinity Measured By Ft/irmentioning
confidence: 84%
“…However, DSC and FT/IR results revealed that the crystallinity of PCL blocks significantly increased and simultaneously that of PE blocks decreased moderately with increasing crystallization time at the late stage. These results suggest the partial melting of PE crystals facilitated by further crystallization of PCL blocks in order to compensate the space previously occupied by amorphous PCL blocks.KEY WORDS: Crystalline-crystalline Diblock Copolymer / Isothermal Crystallization / Morphological Evolution / Crystalline-crystalline diblock copolymers show an interesting morphology formation by the interplay between two kinds of crystallization starting from the microdomain structure formed in the melt.1 There are many studies on the crystallization behavior and resulting morphology of double crystalline diblock copolymers, such as poly("-caprolactone)-blockpoly(ethylene oxide) (PCL-b-PEO), 2-11 poly(p-dioxanone)-15-17 poly(L-lactide)-block-PCL (PLLA-b-PCL), [18][19][20][21][22] and PCL-b-PE. [23][24][25][26][27] In PCL-b-PEO, both blocks have a close melting temperature T m and eventually two kinds of crystallization occur simultaneously to result in a characteristic morphology in the system.…”
mentioning
confidence: 99%